Pengaruh Penggunaan Metode Bernyanyi Terhadap Hafalan Tasrif Pada Mata Kuliah Shorof - Vina Indah Triana; Siti Zahrotul Azizah; Wahyu Hidayat; Dina Indriana (Lembaga Pengembangan Kinerja Dosen, 2025)
Students are required to memorize tashrif in the Shorof course, because tashrif is the main basis in understanding the structure of the Arabic language, especially in word formation and change. Mastery of tashrif helps students recognize the patterns of word changes from roots to derivatives, which is very important for understanding religious texts such as the Qur'an, Hadith, and classical books. In addition, this ability improves reading, writing and speaking skills in Arabic. By memorizing tashrif, students are also more confident in using Arabic actively, both in academic and practical contexts. Therefore, tashrif is an important part of Arabic language learning that not only facilitates text comprehension, but also builds language skills.This study aims to analyze the effect of the singing method on the ability to memorize tashrif in the Shorof course of class 5B students of class 2022. using quantitative approach research with data collection through questionnaires filled out by 28 students. The data obtained were analyzed using descriptive statistics to see the tendency of the influence of the singing method on memorizing tasrif. The use of this singing method is very helpful in improving students' memory in memorizing tasrif. In addition, students consider this method fun and motivate them to be more active in learning.